Effect of berberine on PPARα-NO signalling pathway in vascular smooth muscle cell proliferation induced by angiotensin IV - Hongmei Qiu; Yang Wu; Quanhua Wang; Changqing Liu; Lai Xue; Hong Wang; Qin Wu; Qingsong Jiang (Taylor & Francis Group, 2017)
Context: The available treatments for the abnormal proliferation of vascular smooth muscle cells (VSMCs) are still dismal. Berberine has been demonstrated to possess extensive medicine activity, yet relatively little is known about its effect on VSMCs proliferation. Many studies showed that PPARα and NO participated in the process of VSMCs proliferation. Objective: To evaluate the effect of berberine and its possible influence on PPARα-NO pathway in angiotensin IV-stimulated VSMCs. Materials and methods: The primary VSMCs were cultured with the tissue explants method, and the proliferation was characterized by MTT and protein content. Protein and mRNA expression were measured by Western blot and real-time RT-PCR, respectively. NO synthase (NOS) activity was measured using a spectrophotometric assay, and NO concentration was measured using the Griess assay. Results: Angiotensin IV (0.1 nmol/L)-induced VSMCs proliferation was evidenced by increasing the optical density at A490 and total protein content (p < 0.01), which was inhibited by berberine (10, 30 and 100 μmol/L) in a concentration-dependent manner (p < 0.05). Angiotensin IV decreased the expression of PPARα at mRNA and protein level (p < 0.05), which occurred in parallel with declining eNOS mRNA expression, NOS activity and NO concentration (p < 0.01). Berberine at 30 μmol/L reversed the effects of angiotensin IV in VSMCs (p < 0.05), which were abolished by MK 886 (0.3 μmol/L) (p < 0.05). Discussion and conclusion: The results support the therapeutic effects of berberine on angiotensin IV-induced proliferation in cultured VSMCs at least partially through targeting the PPARα-NO signalling pathway.